Stylistic Devices In The Poetry Of Abdulla Avloni - Sulton Normamatov (International Journal Of Literature And Languages, 2025)
The article examines the linguistic and figurative devices used in the poetic language of the educational reformer and writer Abdulla Avloni. The linguistic features of stylistic tools such as metaphors, similes, comparisons, personification, hyperbole, and attribution found in the poet’s works are analyzed.